Fauna of the brown lacewings of Serbia (Insecta: Neuroptera: Hemerobiidae) - Podlesnik, Jan (Acta entomologica slovenica (Ljubljana), 2019)
The hemerobiid fauna of Serbia was studied during two collecting trips in the years 2015 and 2016. Prior to the present study the hemerobiids in this Balkan country were insufficiently explored. According to literature data and collected material, twenty-three species are listed for the country, of which six are recorded for the first time for Serbia.
Keywords: favna hemerobiidov; hemerobiid fauna; Hemerobiidae; Insecta; lacewings; mrežekrilci; Neuroptera; Serbia; Srbija; Žuželke